KPMG : rebuilding trust in South Africa - Sieff, Grant; Bowen, Amanda (London : Wits Business School, 2020)
By September 2019, six months had passed since KPMG South Africa had released its integrated annual report titled Rebuilding Trust, Redefining Professionalism. Had the company done enough to acknowledge and rectify its legal and ethical lapses, and restore trust?
Description based on XML content.
Keywords: elektronické knihy; electronic books; Corporations -- Finance; Trusts, Industrial, -- South Africa